Analisis Potensi Pemanfaatan Effluent WWTP Kota Jambi Dari Aspek Kuantitas - Munawir Muluk. Z; N. Nurhamidah; Ansiha Nur (Jurnal Serambi Engineering, 2025)
Rapid population growth and climate change have put pressure on water availability, leading to a water crisis. Efforts to control water resources are needed to address this. The option of using domestic wastewater treatment plant effluent has emerged as an alternative solution. In 2024, the Jambi City Wastewater Treatment Plant (WTTP) infrastructure will be constructed and operated with a capacity of 7,500 m^3/day using Moving Bed Biofilm Reactor (MBBR) treatment technology. The existing WTTP is considered to have great potential in terms of volume. However, it is still unknown how much this potential can contribute to meet the water demand of Jambi City. Therefore, this research was conducted to fill this information gap. The research was conducted using the descriptive statistics method with quantitative and qualitative approaches. The analysis of population growth projections and public facilities refers to the Minister of Public Works Regulation No. 18/PRT/M/2007. There are 5 (five) categories of water demand analysed, namely: (a) domestic; (b) general; (c) landscape irrigation; (d) agricultural irrigation; and (e) fisheries. The potential use of wastewater is obtained by comparing the existing wastewater discharge with each category and application of water demand. The results of the analysis show that the effluent from the Jambi City WWTP can contribute 100% to meet the water demand of the domestic category (public taps), public, landscape irrigation and fisheries. In contrast, the domestic category (house connections) can only contribute 11% and the agricultural irrigation category can only contribute 15%.